The Effects of Domestication on Secondary Metabolite Composition in Legumes - Ku, Yee-Shan; Contador, Carolina A.; Ng, Ming-Sin; Yu, Jeongjun; Chung, Gyuhwa; Lam, Hon-Ming (Frontiers in Genetics, 2020)
Legumes are rich in secondary metabolites such as polyphenols, alkaloids, and saponins, which are important defense compounds to protect the plant against herbivores and pathogens, and act as signaling molecules between the plant and its biotic environment. Legume-sourced secondary metabolites are well known for their potential benefits to human health as pharmaceuticals and nutraceuticals. During domestication, the color, smell and taste of crop plants have been the focus of artificial selection by breeders. Since these agronomic traits are regulated by secondary metabolites, the basis behind the genomic evolution was the selection of the secondary metabolite composition. In this review, we will discuss the classification, occurrence and health benefits of secondary metabolites in legumes. The differences in their profiles between wild legumes and their cultivated counterparts will be investigated to trace the possible effects of domestication on secondary metabolite compositions, and the advantages and drawbacks of such modifications. The changes in secondary metabolite contents will also be discussed at the genetic level to examine the genes responsible for determining the secondary metabolite composition that might have been lost due to domestication. Understanding these genes would enable breeding programs and metabolic engineering to produce legume varieties with favorable secondary metabolite profiles for facilitating adaptations to a changing climate, promoting beneficial interactions with biotic factors, and enhancing health-beneficial secondary metabolite contents for human consumption.